X-ray binaries - Lewin, Walter H. G.; Paradijs, J. van.; Heuvel, Edward Peter Jacobus van den, 1940- (Cambridge : Cambridge University Press, 1995)
X-ray binaries are some of the most varied and perplexing systems known to astronomers. The compact object, which accretes mass from its companion star, may be a white dwarf, a neutron star, or a black hole, whereas the donor star can be a 'normal' star or a white dwarf. The various combinations differ widely in their behaviour. This timely volume provides a unique and up-to-date reference of our knowledge of all of them.
This long awaited review provides graduate students and researchers with the standard reference on X-ray binaries for many years to come.
14. A catalogue of X-ray binaries / Jan van Paradijs -- 15. A compilation of cataclysmic binaries with known or suspected orbital periods / Hans Ritter and Ulrich Kolb.
Keywords: X-ray binaries